2008
DOI: 10.1007/s10508-008-9360-y
|View full text |Cite
|
Sign up to set email alerts
|

Familism and Sexual Regulation Among Bisexual Latino Men

Abstract: As the AIDS epidemic continues to disproportionately affect the Latino and African American communities in the United States, little is still known about bisexual behavior and sexual risk of Latino and African American men. This article explores the construct of familism (i.e., the cultural value that weighs on the interdependence among nuclear and extended family members for support, emotional connectedness, familial honor, loyalty, and solidarity) as an analytical point of departure from which to conceptuali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
55
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
3
3
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(62 citation statements)
references
References 39 publications
6
55
1
Order By: Relevance
“…Research has suggested that familismo influences both attitudinal and behavioral norms (Rodriguez & Kosloski, 1998;Sabogal et al, 1987). For example, the embracement of familismo has been associated with sexual decisionmaking among adult Latino men (Muñoz-Laboy, 2008). Specifically, Muñoz-Laboy (2008) found that bisexual Latino males reported that being close to their family and caring about their family's opinions influenced their decisionmaking when selecting sexual and romantic partners.…”
Section: Familismomentioning
confidence: 99%
See 1 more Smart Citation
“…Research has suggested that familismo influences both attitudinal and behavioral norms (Rodriguez & Kosloski, 1998;Sabogal et al, 1987). For example, the embracement of familismo has been associated with sexual decisionmaking among adult Latino men (Muñoz-Laboy, 2008). Specifically, Muñoz-Laboy (2008) found that bisexual Latino males reported that being close to their family and caring about their family's opinions influenced their decisionmaking when selecting sexual and romantic partners.…”
Section: Familismomentioning
confidence: 99%
“…For example, the embracement of familismo has been associated with sexual decisionmaking among adult Latino men (Muñoz-Laboy, 2008). Specifically, Muñoz-Laboy (2008) found that bisexual Latino males reported that being close to their family and caring about their family's opinions influenced their decisionmaking when selecting sexual and romantic partners. In addition, Flores, Eyre, and Millstein (1998) found that Latino youth who embraced the concept of familismo were more likely to prefer romantic partners who valued family and having children.…”
Section: Familismomentioning
confidence: 99%
“…Black and Latino MSM and MSMW may be under additional pressure to deny unwanted CSE as abusive or to appraise abusive experiences as consensual, including those with female perpetrators, since Black and Latino cultures stress the most traditional forms of masculinity [29,32,40,41]. Indeed, these cultural forces may also pressure Black and Latino men to conceal same-sex behavior [29,[42][43][44][45] and to not identify as gay or homosexual [29,[46][47][48]. For these men, CSE with an older male and/or same-sex behavior may be sources of shame and social isolation [44,46,47,[49][50][51].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, these cultural forces may also pressure Black and Latino men to conceal same-sex behavior [29,[42][43][44][45] and to not identify as gay or homosexual [29,[46][47][48]. For these men, CSE with an older male and/or same-sex behavior may be sources of shame and social isolation [44,46,47,[49][50][51]. Further, research suggests that men with histories of sexual abuse are less comfortable with their same-sex attraction than men without such histories [13] and several studies have found that some Black and Latino men who were sexually abused as children experience sexual identity confusion [41,52] or establish a link between their abusive experiences and current same-sex desire [32,50,52].…”
Section: Introductionmentioning
confidence: 99%
“…Three important factors are the role of familismo, acculturation, and religion. Familismo is a one traditional Hispanic value that emphasizes reliance and interdependence on family and community and is believed to be the most important influence in the lives of Latino youth (Contreras, Mangelsdorf, Rhodes, Diener, & Brunson, 1999), even in the context of sexual decision-making (Flores, Tschann, & Marín, 2002;Muñoz-Laboy, 2008).…”
Section: Considerations Of Gender Culture and Racementioning
confidence: 99%